PHYTOCHEMICAL AND BIOLOGICAL STUDIES OF Hellenocarum amplifolium GROWN WILDLY IN SULAYMANIYAH, IRAQ - Qalatopzany, H. S. A.; Lazim, Z. S.; Al-Nashi, T. A. W. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study investigated the phytochemical composition and biological activities of Hellenocarum amplifolium from four regions in Sulaymaniyah Province, Iraqi Kurdistan: Hawraman, Qandil, Penjwin, and Sharbazir. The plant specimens were harvested during the pre-flowering phase, specifically between April and May 2021. Chemical analysis revealed that the Hawraman samples contained the highest levels of phenolics, flavonoids, and bioactive compounds (e.g., gallic acid, quercetin, kaempferol), while Qandil samples were richest in essential oils (e.g., linalool, limonene, α-pinene). Hawraman extracts exhibited the strongest antioxidant activity and provided significant protection against ochratoxin A-induced cytotoxicity. The extract also demonstrated notable antibacterial effects against Escherichia coli at 5000 µg/mL, surpassing some reference antibiotics. These findings highlight H. amplifolium as a promising source of antioxidative and antimicrobial compounds. The study aimed to profile the plant’s phytochemicals, evaluate its antioxidant and antibacterial activities, and assess its protective effects against OTA-induced cytotoxicity.